Ordinary Meaning and the Meaning of Ordinary - Grigorova, Jenya (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2025)
This article proposes a comparative analysis of the practice of adjudicators in the areas of international trade law and international investment law in an attempt to detect commonalities and differences with respect to the method of identifying “the ordinary meaning to be given to the terms of the treaty.” It traces how these adjudicators have understood the concept of ordinary meaning and where they have looked for the “ordinary meaning of the terms of the treaty.” The article also touches upon the question of the timing of the interpreters’ determination of ordinary meaning, and contrasts the concept of “ordinary meaning” to that of “special meaning” in their practice. The comparative analysis allows for the identification, at a very generalized level, of at least two broad trends. First, adjudicators often have the immediate reflex of consulting dictionaries as the starting point of the determination of “ordinary meaning.” Second, regardless of whether these dictionaries have provided them with a satisfactory meaning or not, adjudicators almost immediately proceed to contextualizing this meaning, either as part of their continued quest for the “ordinary meaning” of the interpreted terms, or as part of the next steps in the interpretative process.